The discovery of the bodies of Gervasius and Protasius as comparison of Ambrosius’s assertives, fourth century AD - Pohlmann, Janira Feliciano (Romanitas - Revista de Estudos Grecolatinos, 2014)
In this paper we explore a troubled period in the life of Ambrose, bishop of Milan. Between 385 and 386, this milanese religious leader defied the imperial power of Valentinian II – when denied an imperial petition – and he was questioned and attacked by defenders of the aryan group living in Milan and supported by Justina, mother of the emperor. In a scenario of internal uncertainties and external threats, especially undertaken by Magnus Maximus, Ambrose achieved important successes to his community and reinforced his role as leader. Among the triumphs of this moment, we emphasize the discovery of the bodies of the martyrs Gervasius and Protasius and the consecration of the Basilicam Ambrosianam through these relics.
Keywords: Legitimacy; Ambrose, bishop of Milan; Letters; Gervasius; Protasius